Board Gender Diversity, CEO Characteristics, And Earning Management In The Banking Sector - Salsabilla, Dara; Yossi Diantimala; Indayani; Dinaroe (Jurnal Akuntansi, 2024)
The study examines the effect of board gender diversity and CEO characteristics – CEO age, CEO tenure, and CEO compensation – on earning Management in the banking sector listed on the Indonesian Stock Exchange in 2019-2022. The data of 188 bank– years was obtained from banks’ annual reports taken from the IDX and the bank's official website. Data were analysed by using descriptive statistics and panel data regression. The data fit in with the Common Effect Model (CEM). The results show that earnings management in the banking sector is not caused by gender diversity but is affected significantly by CEO age and tenure. The results support the upper echelon theory. The results fill the gap of previous studies, especially in the banking sector, and provide insight into the role of board gender diversity on earning Management in developing countries that can synthesise the outcome to learn from their governance system.